ANALISIS DAMPAK POLA ASUH OTORITER ORANG TUA TERHADAP PERKEMBANGAN SOSIOEMOSIONAL PADA ANAK USIA SEKOLAH DASAR - Arianita Utami, Putri (Jurnal Pendidikan Dasar Flobamorata, 2024)
Socioemotional development is one of child development. Socioemotional is the development of behavior that occurs in children in controlling emotional conditions and children's ability to respond to their environment. Therefore, during the development period children must continue to be supervised by parents and must provide good parenting for children. Of course, every parenting style has a positive impact and a negative impact, especially authoritarian parenting. The purpose of this study provides a new concept in analyzing the negative and positive impact of authoritarian parenting applied by parents on the socioemotional development of elementary school-age children at the age of 7-12 years. This is done using a literature study method that will explain validly and objectively about the problem analyzed by relying on various sources from various literature such as scientific articles, books and theses. Then it is integrated by analyzing the content (content analysis). The result of this study is to provide reinforcement of data from one another regarding the positive and negative impacts of authoritarian parenting and provide new concepts of thinking about attitudes that can be done by people around children who are cared for authoritarianly.